Analysis of the Use of Toba Batak Traditional Games as BIPA Learning Media - Simanjuntak, Citra Riskya; Putri, Najwa Sabrina; Sitorus, Intan Sri Devi; Banawati, Natasya; Silalahi, Joy Firdaus; Harahap, Safinatul Hasanah (Holistic Science, 2024)
Media is not only a tool to convey material, but also a means that facilitates a more interactive and interesting learning process. Many learning media provided can be applied by educators, one of which is learning media based on traditional Batak Toba games. Therefore, this study discusses the use of traditional Batak Toba games as a BIPA learning medium. The problem in this study is the type of game found in the Batak Toba community, how to use games in the Batak Toba community and the types of games of the Batak Toba community. This study aims to find out the benefits of the traditional game of Batak Toba as well as the types of games in traditional games in Batak Toba. The method used in analyzing this research problem is a qualitative method with a descriptive approach. The types of traditional Toba Batak games are, Mardideng, Pocak Piring, Marsigala, Marroda (hide and seek), and Marsitukkel (engrang). Based on the research conducted, it can be concluded that the traditional Batak Toba game can be used as a learning medium for BIPA teaching. The benefits found from the game from the Batak Toba community are increasing learning motivation, increasing understanding of the material, and interactive learning.